Analisis Pengaruh Teknologi Informasi, Penghargaan (Reward), Disiplin dan Motivasi Terhadap Kinerja Pegawai di KPPD Kabupaten Gunungkidul - Bhre Palasara; Jajuk Herawati; Ignatius Soni Kurniawan (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study is to test the Influence of Information Technology, Employee awards, Work Discipline, Motivation on Employee Performance at the Regional Tax Service Office of Gunungkidul Regency, Yogyakarta (KPPD). This research is a type of quantitative research conducted in the form of questionnaires on employees and staff at KPPD (Regional Tax Service Office of Gunungkidul Regency, Yogyakarta). This study is to analyze the Influence of Information Technology, Employee awards, Work Discipline, Motivation on Employee Performance in the Regional Tax Service Office of Gunungkidul District. To answer research questions and test the hypotheses proposed, multiple linear regression analysis tools are used. The population in this study was all employees and staff (KPPD) of the district. Therewere 40 people with characteristics (age, gender, education graduates, marital status, working age) as research subjects. The results showed that 1). Theology Iof information has a positive and significant effect on Employee Performance, 2). Employee Award has no effect on Employee Performance, 3). Work Discipline does not affect Employee Performance, 4). Work Motivation has a positive and significant effect on Employee Performance at KPPD Gunungkidul. Keywords: Information Technology, Employee Awards, Work Discipline, Work Motivation